Technological vocabulary in the modern Arabic dictionary: Mujam Al-Arabi Al-Asasi/ Mufrodat Tiknuluji fii Al-Mujam Al-Arabi Al-Ashri: Mujam Al-Arabi Al-Asasi - Warahmah, Mawadda; Rosyada, Amrina; Fathoni, Abd Rofi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Advances in science and technology have experienced significant acceleration in various fields, including education. With technological advancements, dictionaries are no longer in the form of physical printouts, but have turned into digital formats that can be accessed through various media. However, a serious challenge in learning and communication in today's digital age is the lack of Arabic dictionaries that cover technological vocabulary. Although technology has brought about major changes in information access, accurate translations of Arabic texts in technological contexts are still difficult to find due to the limitations of electronic dictionaries in capturing grammatical nuances and specialized terminology often used in the field of technology. Therefore, the purpose of this study is to explore the forms of technology vocabulary in the Mujam Al Arabi Al Asasi dictionary. This research uses descriptive method with qualitative approach. The data used comes from sources such as dictionaries, books, journals, or articles relevant to the research context. Data analysis was conducted using qualitative analysis techniques. The results showed that the Mujam Al Arabi Al Asasi dictionary has suitability with the research material, namely technological vocabulary, which is divided into technological, economic, and social aspects.Keywords: vocabulary; technology; arabic dictionary